Update in Laboratory Diagnosis of Urinary Tract Infection - Weny Rinawati; Diana Aulia (Jurnal Penyakit Dalam Indonesia)
Urinary tract infection (UTI) is an infection caused by the entry of pathogens into the urinary tract. Symptoms of a UTI are not always obvious, and some are asymptomatic or atypical. Urinary tract infections must be distinguished from other diseases that have a similar clinical appearance. Many UTIs resolve spontaneously, but often cause significant morbidity and mortality. With the unpredictable nature of the disease, laboratory tests are required for accurate diagnosis and identification of the cause of infection. Thus, it is necessary to understand the interpretation and limitations of urinalysis and urine culture results. To assist in the diagnosis of urinary tract infections, flowcytometry is currently being developed. With the ability to detect bacteria, this tool can be used for UTI screening in the pre-analytic phase of urine culture.